An Evaluation of Safety Standards of E/E/PES Systems Regarding Information Consistency & Enhancement Proposals - Dogruguven, Ersin H.; Ustoglu, Ilker (IEEE, 2019)
This paper makes an evaluation of the safety standards of electrical/electronic/programmable electronic safety-related systems (E/E/PES) with regards to consistency of the information provided in these standards and their applicability. It provides open discussion and proposals for essential moot questions utilizing experiences gained in various safety-critical projects in long years, especially in the railway industry. IEC 61508 and CENELEC EN 50126, 50128 and 50129 are used as safety standards in this study.
Keywords: functional safety; safety standards; IEC 61508; CENELEC; HR; CCF; SIL; Engineering